Study on the Effectiveness of Healthcare Software Used By the Doctors during the Pandemic - MUTHUKRISHNAN, R; PREETHIKA, P.; MUGILARASU, S.; SIVABALAN, M. (The journal of contemporary issues in business and government, 2021)
In this project, we describe some of the key observations resulting from our work on using Bajaj Finserv Health DoctorRX platform to help and detect effectiveness of PMS (Practice Management system) processes and usage of platform among doctors. In many ways, medical processes are similar to distributed systems in their complexity and proneness to contain errors. We have been investigating the application of a DoctorRX platform for improvement and to make approach the medical processes in much easier way and so that it is subjected to rigorous analyses. The technologies we applied helped improve understanding about the processes and led to the detection of errors and subsequent improvements of the platform. This work is still preliminary, but is suggesting new research directions for improvement, and effectiveness of platform along with, and the applicability of this available system. Doctors have one of the most demanding jobs in the world – structuring up treatment plans, attending to patients, charting the job plan, clerical work, and keeping updated with the most recent advancements in the field of medical technology. Doctors are our marvel workers on this planet Earth and sure seem to have their hands full at all given times. However, with the coming up of modern technology encircling all aspects of life, it is no revelation that there are a numerous time-saving expedient software for doctors like Practo, pMD, Prescription pad, etc., In this project, Doctor RX platform has been taken into consideration to understand in depth the process that is carried out.